2017
DOI: 10.4103/0022-3859.191008
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial mural thrombi

Abstract: Background:Right atrial mural thrombi (RAMT) are often seen in association with cardiac diseases or foreign bodies. Unusual locations at the flutter isthmus and the atrial appendage prompted us to evaluate our 2-year autopsy data on such thrombi.Materials and Methods:In the 2-year retrospective autopsy, the clinical and autopsy records of patients with RAMT were reviewed, with particular reference to the presence of central venous catheter (CVC), its site of insertion, its type, material and size, its duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In contrast, type B thrombi are often stationary, fixed to the right atrial wall, and less susceptible to thrombolysis [8,10]. They are uncommon in a structurally normal heart but can however occur in hypercoagulable states, right atrial catheterization, pacemaker implantation, low cardiac output states, septal closure devices, cardiac trauma, cardiomyopathies, indwelling central venous lines, cardiac arrhythmias, neoplastic processes, and some systemic diseases [8,11,12]. They are generally associated with a favourable prognosis given that they are often adherent to the right atrial wall and are less likely to embolize, thus making them a low-risk group compared to type A [3,13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, type B thrombi are often stationary, fixed to the right atrial wall, and less susceptible to thrombolysis [8,10]. They are uncommon in a structurally normal heart but can however occur in hypercoagulable states, right atrial catheterization, pacemaker implantation, low cardiac output states, septal closure devices, cardiac trauma, cardiomyopathies, indwelling central venous lines, cardiac arrhythmias, neoplastic processes, and some systemic diseases [8,11,12]. They are generally associated with a favourable prognosis given that they are often adherent to the right atrial wall and are less likely to embolize, thus making them a low-risk group compared to type A [3,13].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of 30 non-atherosclerotic and non-aneurysmal aortic thrombosis events identified that 47% of the cases involved the abdominal aorta. 14 The majority of cases occurred between the third and fourth decade of life. Primary causes were attributed to hypercoagulable states and aortic wall changes.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three of these patients had CVC insertion before death. 1 The back-and-forth motion of the catheter within the RA cavity is believed to produce mechanical trauma in the RA, predisposing to mural thrombus formation. The prior history of prolonged CVC placement for chemotherapy in our case may have predisposed for thrombus formation; however, catheter placement and thrombosis were remote (18 years prior).…”
Section: Discussionmentioning
confidence: 99%